Propionic acidemia: neonatal versus selective metabolic screening - Grünert, Sarah; Lindner, Martin (Journal of inherited metabolic disease, 2012)
BackgroundWhereas propionic acidemia (PA) is a target disease of newborn screening (NBS) in many countries, it is not in others. Data on the benefit of NBS for PA are sparse.Study designTwenty PA patients diagnosed through NBS were compared to 35 patients diagnosed by selective metabolic screening (SMS) prompted by clinical findings, family history, or routine laboratory test results. Clinical and biochemical data of patients from 16 metabolic centers in Germany, Austria, and Switzerland were evaluated retrospectively. Additionally, assessment of the intelligent quotient (IQ) was performed. In a second step, the number of PA patients who have died within the past 20 years was estimated based on information provided by the participating metabolic centers.ResultsPatients diagnosed through NBS had neither a milder clinical course regarding the number of metabolic crises nor a better neurological outcome. Among NBS patients, 63% were already symptomatic at the time of diagnosis, and <10% of all patients remained asymptomatic. Among all PA patients, 76% were found to be at least mildly mentally retarded, with an IQ <69. IQ was negatively correlated with the number of metabolic decompensations, but not simply with the patients’ age. Physical development was also impaired in the majority of patients. Mortality rates tended to be lower in NBS patients compared with patients diagnosed by SMS.ConclusionEarly diagnosis of PA through NBS seems to be associated with a lower mortality rate. However, no significant benefit could be shown for surviving patients with regard to their clinical course, including the number of metabolic crises, physical and neurocognitive development, and long-term complications.
First online: 02 December 2011
Gesehen am 19.06.2018